Pengaruh Konsep Diri, Praktek Kerja Lapangan Dan Informasi Dunia Kerja Terhadap Kesiapan Kerja Mahamahasiswa Program Studi Akuntansi - ., Handika Asep Kurniawan (CV. ITTC INDONESIA, 2022)
This study aims to determine: (1) the positive and significant influence of self-concept on student work readiness, (2) the positive and significant influence of field practice on student work readiness, (3) the positive and significant influence of information on the world of work on student work readiness, (4) the positive and significant influence of self-concept, field practice and information on the world of work together on student work readiness.This research is a type of ex post facto research. The population in this study were 52 students of accounting study program. Data collection techniques using questionnaires and documentation. Data were analyzed by simple regression technique and multiple regression analysis.The results of this study indicate that at a significance level of 5%. (1) There is a positive and significant influence of self-concept on work readiness with of 8,141. (2) There is a positive and significant influence field practice on work readiness with of 6,420. (3) There is a positive and significant influence between information on the world of work on work readiness and of 5,947. (4) There is a positive influence and significant self-concept, field practice and information on the world of work together on work readiness with of 29,011.